(untitled) (Research, Society and Development, 2020)
The practice of physical exercises is of fundamental importance for people’s health and quality of life. In this context, resistance weight training exercises are among the most suitable for the most diverse age groups. The objective of the present study was to verify the profile of users who attend weight training gyms. For this, a random sample of 23 gyms, from the city of Uberlândia MG, was used. To obtain the results, a survey was carried out with the databases of the academies, where the numbers of students enrolled in the bodybuilding modality were checked. The prerequisite for the inclusion of the student’s data in the research was that he / she was a regular user of the gym, in the bodybuilding modality, for a period equal to or greater than 6 (six) months. A total sample of 2639 bodybuilding students was obtained, of these 1351 (51.2%), belonging to the male gender and 1288 (48.8%) to the female gender. Then they were divided into age groups: up to 20 years; (21-30 years); (31-40 years); (41-50 years); (51-60 years); over 60 years. After tabulation and analysis of the collected data, the following results and conclusions were reached: as for gender, there was minimal difference, with the male being 2.4% higher; in relation to the age groups in both genders, the age group 21-30 years was considerably larger, male (27.3%) and female (28.3%), the vast majority of students (71.01%) are in the age groups up to 40 years of age. The findings of the present study show that the general public of weight training gyms is composed of young people.